A National Survey of Hepatocellular Carcinoma Surveillance Practices Following Liver Transplantation. Issue 1 (January 2021) - Aggarwal, Avin; Te, Helen S.; Verna, Elizabeth C.; Desai, Archita P.
Abstract : Background: Recurrence of hepatocellular carcinoma (HCC) is an important predictor of survival after liver transplantation (LT). Recent studies show that early diagnosis, aggressive treatment, and surveillance may improve outcomes after HCC recurrence. We sought to determine the current practices and policies regarding surveillance for HCC recurrence after LT. Methods: We conducted a web-based national survey of adult liver transplant centers in the United States to capture center-specific details of HCC surveillance post-LT. Responses were analyzed to generate numerical and graphical summaries. Results: Of 101 eligible adult liver transplant centers, 48 (48%) centers across the United States responded to the survey. Among the participating centers, 79% stratified transplant recipients for HCC recurrence risk, while 19% did not have any risk stratification protocol. Explant microvascular invasion (mVI) was the most common factor used in risk stratification. Use of pretransplant serum biomarkers such as alpha-fetoprotein (AFP) was variable, with only 48% of the participating centers reporting specific "cutoff" values. While a majority of centers (88%) reported having a routine imaging protocol for HCC recurrence surveillance, there was considerable heterogeneity in terms of frequency and duration of such surveillance. Of the centers that did risk stratify patients to identify those at higher risk of HCC recurrence, about 50% did not change their surveillance protocol. Conclusions: Our study affirms significant variability in center practices, and our results reflect the need for high-quality studies to guide risk stratification and surveillance for HCC recurrence.